Solitary Learning Style in Writing Narrative Text at MAN 1 Kota Gorontalo - Firman A. Mahyudin; Nonny Basalama; Zulkifli Tanipu (Transbahasa, 2024)
This research explores solitary learning styles among students in the context of writing narrative texts at MAN 1 Kota Gorontalo. In a diverse educational environment, understanding different learning styles is crucial for educators to meet the varied needs of students. Solitary learning allows students to engage with content independently, potentially revealing unique insights into how students express themselves and develop their writing skills. This research employs a qualitative descriptive method to collect data through questionnaires and interviews to identify individual students' learning preferences. The findings indicate that students who engage in solitary learning exhibit enhanced abilities in writing narrative texts, with increased focus and improved management of their learning processes. This research indicates a pressing need to develop more effective and inclusive teaching strategies specifically designed to support solitary learners and provide valuable guidance for curriculum developers in designing appropriate and relevant materials.